2019
DOI: 10.1002/ecy.2658
|View full text |Cite
|
Sign up to set email alerts
|

Migration triggers in a large herbivore: Galápagos giant tortoises navigating resource gradients on volcanoes

Abstract: To understand how migratory behavior evolved and to predict how migratory species will respond to global environmental change it is important to quantify the fitness consequences of intra‐ and inter‐individual variation in migratory behavior. Intra‐individual variation includes behavioral responses to changing environmental conditions and hence behavioral plasticity in the context of novel or variable conditions. Inter‐individual variation determines the degree of variation on which selection can act and the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 34 publications
(103 reference statements)
1
26
0
1
Order By: Relevance
“…), though this trend has also been observed for terrestrial herbivores (Bastille‐Rousseau et al. ). Analogous long‐range strategies have been observed for migratory red deer that “jump the green wave” to maximize resources at the end of their migration (Bischof et al.…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…), though this trend has also been observed for terrestrial herbivores (Bastille‐Rousseau et al. ). Analogous long‐range strategies have been observed for migratory red deer that “jump the green wave” to maximize resources at the end of their migration (Bischof et al.…”
Section: Introductionmentioning
confidence: 55%
“…In contrast, many long-distance migrants cannot rely on local information and must anticipate disparate, often unpredictable changes in the seasonality of abiotic conditions and vegetation phenology from great distances to encounter favorable conditions and exploit maximum resources. This is particularly true for birds (Both et al 2009, Møller et al 2010), many of which are shifting the timing of their arrival to breeding grounds to match changes in local climate and phenology (Cotton 2003, Marra et al 2005, Rubolini et al 2007, Barrett 2011, Ward et al 2016, though this trend has also been observed for terrestrial herbivores (Bastille-Rousseau et al 2019). Analogous long-range strategies have been observed for migratory red deer that "jump the green wave" to maximize resources at the end of their migration (Bischof et al 2012), and for zebras (Equus burchelli), that show evidence of memory-based forecasting of water resources (Bracis and Mueller 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Data sets generated by RTLSs are incredibly versatile and can be used in conjunction with other geographic data (e.g., remotely sensed data) to answer a wide variety of ecological research questions pertaining to individual‐ and population‐level animal behaviors (Kays, Crofoot, Jetz, & Wikelski, 2015). Previous studies have used RTLS data to draw inferences about (a) animals' movement speed and tortuosity (Bastille‐Rousseau et al, 2019; Liu, Xu, & Jiang, 2015; Schiffner, Fuhrmann, Reimann, & Wiltschko, 2018), (b) energy expenditures (Williams et al, 2014), (c) habitat use (Keeley, Beier, & Gagnon, 2016; Thomson et al, 2017; Tsalyuk, Kilian, Reineking, & Marcus, 2019), (d) survival and mortality rates (Klaassen et al, 2013), (e) responses to environmental stimuli (Bastille‐Rousseau et al, 2019; Tsalyuk et al, 2019), and (f) interactions with other individuals, specific locations, or environmental substrates (Chen, Sanderson, White, Amrine, & Lanzas, 2013; Chen & Lanzas, 2016; Dawson, Farthing, Sanderson, & Lanzas, 2019; Spiegel, Leu, Sih, & Bull, 2016; Theurer et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Much research has been conducted to assess the ecology, biology and genetics of giant tortoises, whereas very little is known about the health status of these species. Current threats include habitat loss and fragmentation, illegal trade, introduced and invasive species, global warming, egg loss due to introduced predators, disease, trauma and possibly antimicrobial resistance ( Blake et al , 2012 ; Ellis-Soto et al , 2017 ; Bastille-Rousseau et al , 2019 ; Nieto-Claudin et al , 2019 ). Several studies have been published to describe RI for chelonian species globally; however, there was only one study on giant tortoises describing haematology and blood biochemistry parameters for 32 giant tortoises ( Chelonoidis chathamensis ) at a captive-breeding facility on San Cristóbal Island ( Lewbart et al , 2018 ), and no morphological evaluation of blood cells was documented.…”
Section: Introductionmentioning
confidence: 99%